γ-Tocotrienol induces paraptosis-like cell death in human colon carcinoma SW620 cells. - Jing-Shu Zhang (Public Library of Science (PLoS), 2013)
Colorectal cancer is one of the most serious illnesses among diagnosed cancer. As a new type of anti-cancer composition from tocotrienol-rich fraction of palm oil, γ-tocotrienol is widely used in anti-cancer research. The objectives of this study were to investigate the effects of γ-tocotrienol on human colon cancer SW620 and HCT-8 cells. We showed that treatment with different concentrations of γ-tocotrienol resulted in a dose dependent inhibition of cell growth. Cell death induced by γ-tocotrienol was mediated by a paraptosis-like cell death in SW620 and HCT-8 cells. Real-time RT-PCR and western blot analyses showed that γ-tocotrienol inhibited the expression level of β-catenin, cyclin D1 and c-jun. These data suggest that a paraptosis-like cell death induced by γ-tocotrienol in SW620 cells is associated with the suppression of the Wnt signaling pathway, which offers a novel tool for treating apoptosis-resistance colon cancer.